Bhāṭṭabhāskara - Jīvadeva; Śarmā, Kamalanayana.; Ganganatha Jha Kendriya Sanskrit Vidyapeetha. (Bhāṭṭabhāskara, 1996)
Classical work on Mimamsa philosophy.
Includes bibliographical references (p. [499]-510) and indexes.
Classical work on Mimamsa philosophy.
In Sanskrit; introd. in English.
Keywords: Mimamsa / Early works to 1800 / http://id.loc.gov/authorities/subjects/sh2008107808